Effect of feeding frequency on water quality, growth, and hematological parameters of Nile tilapia Oreochromis niloticus reared using biofloc technology. Issue 2 (3rd April 2021) - Hisano, Hamilton; Pinheiro, Victor Rossi; Losekann, Marcos Eliseu; Moura e Silva, Mariana Silveira Guerra
ABSTRACT: The aim of this study was to evaluate the effect of feeding frequency on water quality, growth performance, feed efficiency, and hematological parameters of Nile tilapia reared in biofloc technology (BFT) over a period of 45 days. Fish (n = 6, 480; 5.36 ± 1.45 g) were randomly distributed in nine outdoor circular tanks (9, 000 L) with individual air-water lift by supplementary aeration and hand-fed with commercial diet (32% crude protein) at 5-3% of biomass, following the respective feeding frequencies: two times per day, four times per day, and six times per day. The experimental design was completely randomized with three treatments and three replicates. Feeding frequency at four times per day decreased rotifer density and improved ( P < .05) the weight gain and protein efficiency ratio. No significant differences were observed in hematological parameters. Water quality remained within recommended ranges for tilapia culture. Turbidity and floc volume showed significant differences ( P < .05) among treatments, with the greatest concentrations at six times per day. Feeding frequency at four times per day promoted the best growth and feed efficiency responses in Nile tilapia (5 - 20 g)cultured in BFT.